Evaluation of Hydrogen Utilization for Catalytic Hydrodeoxygenation of Residual Biomass Pyrolysis Oil at Atmospheric Pressure - Lorenzo Bartolucci; Stefano Cordiner; Massimiliano Materazzi; Pietro Mele; Vincenzo Mulone; Hualun Zhu (Chemical Engineering Transactions, 2024)
Biomass is an abundant renewable energy resource that can be converted into carbon-based biofuels. Pyrolysis is a thermochemical process that allows the rapid conversion of residual biomass and biowaste into bio-oil, a liquid biofuel with a high energy density. Hydrodeoxygenation (HDO) is a catalytic process in which typically high-pressure hydrogen is used to remove oxygen mainly through dehydration, decarboxylation and decarbonylation reactions from the oxygenated compounds of bio-oil. The objective of this work is to evaluate the process of hydrodeoxygenation under mild conditions, i.e. atmospheric pressure, quantifying the hydrogen consumption and the degree of deoxygenation. The organic fraction of the pyrolysis oil of spent coffee grounds has been processed in a packed-bed reactor in a semi-continuous regime. The performance of two different MoO3/NiO alumina-supported catalysts were evaluated at 350°C and LHSV of 0.5. The results showed a high upgraded oil yield (72-87 w/w %), limited gas production (up to 1 w/w%) and a limited coking (12-26 % w/w). GC-MS analysis of upgraded oil showed a significant reduction of hydrocarbons molecular weight, as well as caffeine, fatty acids and furans relative concentration, while pyridines, phenolics and ketones were still very abundant. The measured hydrogen consumption was very limited (up to 1g/L bio-oil), suggesting that increasing pressure would be beneficial for higher degree of deoxygenation.